2017
DOI: 10.5999/aps.2017.01025
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of Infected Breast Implants

Abstract: BackgroundImplant-based breast reconstruction is being performed more frequently, and implants are associated with an increased risk of infection. We reviewed the clinical features of cases of implant infection and investigated the risk factors for breast device salvage failure.MethodsWe retrospectively analyzed 771 patients who underwent implant-based breast reconstruction between January 2010 and December 2016. Age, body mass index, chemotherapy history, radiation exposure, and smoking history were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 11 publications
4
31
1
2
Order By: Relevance
“…Our data showed a 46.2% prosthesis salvage rate for SSIs that were treated with parenteral antibiotics only. Our salvage rate is comparable to those reported by other authors who have employed both surgical and medical treatments [ 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our data showed a 46.2% prosthesis salvage rate for SSIs that were treated with parenteral antibiotics only. Our salvage rate is comparable to those reported by other authors who have employed both surgical and medical treatments [ 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…In turn, in the work of Chidester et al (2016) P. aeruginosa was the most common causative agent of infections and accounted for 26.8% of them. Research carried out by Song et al (2017) indicates the involvement of A. baumanii in infections alongside with P. aeruginosa. In our work more frequently than in the previous studies (Feldman et al 2010;Seng et al 2015;Chidester et al 2016;Song et al 2017), Gram-negative bacilli were isolated.…”
mentioning
confidence: 99%
“…One of the reasons for salvage failure is the suboptimal treatment of MRSA infection. According to a report by Song et al [ 21 ], MRSA is the most commonly identified strain in implantrelated infections and an important factor for explantation. Yii and Khoo [ 22 ] confirmed that the salvage rate was lower in breast reconstructions with MRSA infection.…”
Section: Discussionmentioning
confidence: 99%
“…Yii and Khoo [ 22 ] confirmed that the salvage rate was lower in breast reconstructions with MRSA infection. A study of 69 patients with infected or exposed breast implants by Spear and Seruya in 2010 reported that infection with Gram-negative rods, MRSA, and Candida parapsilosis was associated with a higher probability of salvage failure [ 15 , 21 ]. The infection sources could include community-acquired pathogens and contamination from medical staff who participated in the operation.…”
Section: Discussionmentioning
confidence: 99%